Standardization of Unani Compound Formulation Zimad-e-Roos - Thanuja, G.; Muthalib, A.M. (Faculty of Indigenous Medicine, University of Colombo, 2025)
Standardization is a crucial process to ensure the quality, safety, and efficacy of Traditional Medicine. Despite its therapeutic value, the Unani system lacks standardization for many formulations, leading to batch-to-batch variability. This study aims to standardize Zimad-e-Roos, an Unani polyherbal formulation traditionally used in the management of joint disorders such as Waja-ul-Mafasil (Arthralgia), Waja-ul-Zohr (Backache), Thahajjarul Mafasil (Rheumatism) and Hadhar (like Carpal Tunnel Syndrome). Zimad-e-Roos comprises Maghz-e-Tukhm-eBedanjeer (seed kernel of Ricinus communis), Asal (Bee honey), and Roghan-e-Gao (Ghee). The formulation was prepared in accordance with the National Formulary of Unani Medicine, Volume 04. Quality evaluation was performed using Organoleptic, Physicochemical, and Phytochemical analyses according to Quality Control Methods for Medicinal Plant Materials and herbal formula - World Health Organization (WHO), 1998, Indian Pharmacopoeia - Ministry of Health and Family Welfare, Government of India and Ayurvedic Pharmacopoeia of India- Government of India, Ministry of AYUSH Organoleptic characteristics revealed a light brown color, characteristic odour, and moderately fine texture. Physicochemical analysis showed a Total ash value of 12.5± 0.3% and Moisture content 7.28%. Phytochemical screening confirmed the presence of active constituents such as Tannins, Phenols, Flavonoids, Terpenoids, Saponins, Carbohydrates, and Reducing sugars. The results confirm that Zimad-eRoos can be standardized using defined quality parameters, which will support consistency in preparation, enhance therapeutic efficacy, and establish quality control protocols. The findings may serve as a reference for future studies and standardization of similar Unani formulations.
Keywords: Standardization; Zimad-e-Roos; Maghz-e-Tukhm-e-Bedanjeer; Asal; Roghan-e-Gao